Electrodeposition of kesterite thin films for photovoltaic applications: Quo vadis?. Issue 1 (3rd December 2014) - Colombara, D.; Crossay, A.; Vauche, L.; Jaime, S.; Arasimowicz, M.; Grand, P.‐P.; Dale, P. J.
Abstract This paper aims at providing an updated overview of the main achievements in the development of solar cells based on Cu2ZnSn(S, Se)4 (CZTS(Se)) kesterite absorbers obtained by electrodeposition. Although undoubtedly challenging, the ultimate goal is to learn from the past works and build a solid framework for future advances in this field. What is the reason for the lower efficiency of electrodeposited CZTS(Se)‐based devices (8%) compared to the world record efficiency achieved with a hydrazine‐based solution approach (12.6%)? Can this gap be filled, or there are intrinsic limitations for this achievement? The review is divided into the three main electrodeposition approaches: sequential elemental layer, alloy co‐deposition, and chalcogenide co‐deposition. It is argued that considerable technical challenges must be overcome for the latter approach to be successfully applied. <inline-graphic xlink:href="ark:/27927/pgh3730r220" content-type="pssa201431364-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Plot of the record power conversion efficiencies of kesterite sulfide‐based solar cells obtained by electrodeposition (hollow dots), and world record efficiency of CZTS(Se)‐based devices (full dots). The dashed line shows the 15% minimum efficiency threshold considered relevant for potential industrial application.